49 up [videorecording (DVD)] - Apted, Michael; Balden, Bruce; Bassett, Jacqueline; Basterfield, Symon (Apted, Michael. Up series., 2006)
The seventh installment in Michael Apted's Up Series. In 1964, 14 children from diverse backgrounds were interviewed about their lives and dreams. Every seven years, Apted has been back to talk to them, examining the progression of their lives.